Optimal Data Transfer Over RIS-Assisted Edge Networks Using Coordinated 3D Beamforming - Tripathi S.; Pandey O.J.; Hegde R.M. (My University, 2025)
In a multi-cell network, the cell-edge users (CEUs) usually suffer from low data throughput and poor signal-to-noise-plus-interference-ratio (SINR) due to being placed far away from the base stations (BSs). To address these challenges, in this work, a reconfigurable intelligent surface (RIS)-assisted coordinated 3D beamforming method is proposed to improve the data throughput of the CEUs over a multi-cell network. RISs are programmable meta-surfaces that enable the control of wireless propagation characteristics of the wave incident on them. In particular, in this work, the impact of RIS elements' amplitude and practical phase-shift model are investigated on the overall network SINR and required transmit power. The method develops a practical power management scheme during coordinated 3D beamforming over the CEUs, resulting in minimized power consumption across the network. Moreover, exploiting the property of the RIS, an optimization problem is formulated to maximize the SINR of the CEUs with respect to the coordinating BSs antenna downtilt angle, practical reflection properties of the RIS, and total transmitted power. Due to the intractable nature of the optimization problem, an alternating optimization (AO) algorithm is presented to optimize the SINR. Finally, extensive simulation results are obtained, demonstrating the proposed method's effectiveness over other existing methods. © 2023 IEEE.